2-ZZ=0.03+0.08111

Add 0.03 and 0.08111.

2-ZZ=0.11111

Multiply each term by Z and simplify.

Multiply each term in 2-ZZ=0.11111 by Z.

2-ZZ⋅Z=0.11111⋅Z

Cancel the common factor of Z.

Cancel the common factor.

2-ZZ⋅Z=0.11111⋅Z

Rewrite the expression.

2-Z=0.11111⋅Z

2-Z=0.11111Z

2-Z=0.11111Z

Move all terms containing Z to the left side of the equation.

Subtract 0.11111Z from both sides of the equation.

2-Z-0.11111Z=0

Subtract 0.11111Z from -Z.

2-1.11111Z=0

2-1.11111Z=0

Subtract 2 from both sides of the equation.

-1.11111Z=-2

Divide each term by -1.11111 and simplify.

Divide each term in -1.11111Z=-2 by -1.11111.

-1.11111Z-1.11111=-2-1.11111

Cancel the common factor of -1.11111.

Z=-2-1.11111

Divide -2 by -1.11111.

Z=1.800001‾

Z=1.800001‾

Z=1.800001‾

Solve for Z (2-Z)/Z=0.03+0.08111